Jakiej teorii prawdy relatywiści potrzebują? - Witek, Maciej (Filozofia Nauki, 2003)
The aim of this paper is to justify the claim that relativism assumes a deflationary account of truth. In the first section the author articulates some terminological conventions regarding the use of the terms "relativism" and "deflationism". It is assumed that relativism advocates two theses. The first one is the thesis of relativity. It says that opinions adopted by members of some community depend on social or cultural factors determining their cognitive point of view. The second one is the thesis of symmetry. It claims that the idea of the absolute and objective correctness has no sense. In other words, the choice of a cognitive point of view cannot be objectively justified. Nevertheless, it can be explained by describing its social causes. Next, the author analyses the most popular deflationary views on truth. It is assumed that the most reliable form of deflationism is the so-called disquotational conception. According to the conception in question the meaning of a concept of truth is entirely captured by instances of the disquotational scheme: "S" is true if and only if s. It is stressed that the instances of the scheme define the immanent notion of truth. The point is that the notion so defined can be predicated only on sentences one understands. In the second section the author develops the main argument of this paper. A few relativistic accounts of truth are analysed. It is argued that relativists have no alternative but to accept the deflationary account of truth. The main idea of the argument is that rejecting the notion of transcendent truth relativism makes the notion of truth empty and strictly immanent. In other words, it makes the notion deflationary. The third section contains some remarks on possible ways of arguing against relativism.